Management of Intranatal Care Health Services for Premature Rupture of Membranes at the Happy Minasaupa Mother and Child Hospital - Kadir, Erni; Verawati, Verawati; Dwi Rahmawati, Agustini Liviana; Ekawati, Nur; Masita, Syarifah; MS, Nur Hidayah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Maternal death due to complications during childbirth or infection after childbirth is a fact of life throughout human history, but improvements in medical services have resulted in significant reductions in maternal mortality in developed countries. Until now, maternal mortality is still one of the priority issues in the field of maternal and child health in Indonesia. Every one hour two mothers in Indonesia die during childbirth due to various causes. The direct causes of maternal death in Indonesia are bleeding, infection and eclampsia. The purpose of this study was to identify and analyze basic data and to evaluate the need for immediate action on premature rupture of membranes at the Happy Minasaupa Mother and Child Hospital, Makassar. The research method used was Varney's seven-step method which included identification of basic data, formulating diagnoses, interventions, implementation and evaluation of midwifery care for women in labor with premature rupture of membranes and documentation. Conclude that the goals of midwifery care applied are achieved as expected.